H HUBUNGAN PERILAKU PERAWATAN KAKI TERHADAP KEJADIAN ULKUS KAKI DIABETIK - Manto, Onieqie Ayu Dhea; Nestriani, Ni Wayan Elsi Nestriani; Latifah, Latifah (LPPM Universitas Sari Mulia, 2023)
Background: One of the chronic complications of type 2 diabetes mellitus is diabetic foot ulcers. The incidence of foot ulcers in Indonesia is quite high, reaching 7%-24% and is a problem that has not been resolved properly. The efforts to prevent and reduce the incidence of diabetic foot ulcers are by foot care behavior. Objective: To determine the relationship between foot care behavior towards the incidence of diabetic foot ulcers at Dr. H. Moch Ansari Saleh Banjarmasin Hospital. Method: : Quantitative method with cross sectional design. The population in this study amounted to 203 people. The sample was 20% of the population, which is 41 respondents. The sampling technique in this study is using purposive sampling. Result: Spearman Rank correlation test results with = 0,05. The results of the analysis of the relationship between foot care behavior and the incidence of ulcers showed p=0.000 and a correlation coefficient is -0.589. Conclusion: There is a strong unidirectional relationship between foot care behavior towards the incidence of Diabetic Foot Ulcers at Dr. H. Moch. Ansari Saleh Banjarmasin Hospital. Keywords: diabetic foot ulcer, foot care